The debatable role of singlet oxygen in persulfate-based advanced oxidation processes - Wang, Liangjie; Xiao, Ke; Zhao, Huazhang (Water research (Oxford), 2023)
•The basic properties of 1O2 are introduced.•The formation of 1O2 and its reaction with organics are summarized.•The debatable roles of 1O2 in PS-AOPs are discussed.•The methods and their drawbacks of 1O2 identification are analyzed.•Prospects about the rational identification of 1O2 are put forward. Singlet oxygen (1O2) attracts much attention in persulfate-based advanced oxidation processes (PS-AOPs), because of its wide pH tolerance and high selectivity toward electron-rich organics. However, there are conflicts about the 1O2 role in PS-AOPs on several aspects, including the formation of different key reactive oxygen species (ROS) at similar active sites, pH dependence, broad-spectrum activity, and selectivity in the elimination of organic pollutants. To a large degree, these conflicts root in the drawbacks of the methods to identify and evaluate the role of 1O2. For example, the quenchers of 1O2 have high reactivity to other ROS and persulfate as well. In addition, electron transfer process (ETP) also selectively oxidizes organics, having a misleading effect on the identification of 1O2. Therefore, in this review, we summarized and discussed some basic properties of 1O2, the debatable role of 1O2 in PS-AOPs on multiple aspects, and the methods and their drawbacks to identify and evaluate the role of 1O2. On the whole, this review aims to better understand the role of 1O2 in PS-AOPs and further help with its reasonable utilization. [Display omitted]